Experimental and multiphysics simulation study of atoms migration and morphology evolution in solder joints under high current density. (March 2023) - Jia, Fei; Niu, Leyi; Xi, Yuchen; Qiu, Yuanying; Ma, Hongbo; Yang, Chengpeng
Highlights: X-ray CT results show the number of voids decreases with voids size, volume and area. Most voids appear as distributed and small size near the inlet of electron flow. A 3D model combined atom diffusion, heat transfer, current and mechanics is developed. The atomic concentration gradient plays an increasing role in atoms migration. Voids formation cause much uneven heat flux distribution and the earlier EM failure. Abstract: Voids in solder joints induced by electromigration significantly affect the mechanical and electrical properties of materials, causing performance degradation and reduction in durability of electronic devices. In this study, atoms migration behavior and both voids formation and heat transfer characteristics under high current density are investigated by experiments and dynamic multiphysics simulations. In experiments, the solder joint voltage and temperature distribution are measured in situ. Besides, X-ray CT images are utilized to observe the morphology of solder joints and quantitively analyze the volume, surface area and size distribution of voids. The experimental results show that voids mainly appear in small size and distribute near the inlet of electron flow. With the increase of voids volume and area, the number of voids significantly decreases; while the number of voids falls slowly as the equivalent diameter increases. Meanwhile, a three-dimensional model combined atoms diffusion, transient heat transfer, current density, and mechanical response is developed. The model is validated by experimental results and modeling results show that atoms migrate from the cathode to the anode, causing current crowding to occur and the maximum values of tensile stress and temperature at the cathode side to locate at voids region. With the decrease of atomic concentration at the cathode, voids propagate and block the heat transfer path, leading to much uneven heat flux distribution and higher thermal resistance of the bump. Considering the effect of voids space on the microstructure of the bump, the rate of voids propagation is improved and the electromigration failure occurs earlier.